The Effect of Compensation, Leadership and Organizational Culture Through Work Motivation on Employee Performance - Djoko Setyo Widodo (Jurnal Manajemen dan Kewirausahaan, 2017)
This study aims to examine the effect of compensation, leadership and organizational culture through work motivation on employee performance. This study uses a quantitative method by distributing questionnaires to employees in the conventional banking environment in Bekasi. The research sample is determined by simple random sampling and the technique analysis is SEM analysis with AMOS ver. 21. This study shows positive and significant results partially from the effect of variable compensation, leadership, organizational culture and motivation on employee performance. On the other hand, the study also find that organizational culture has no effect on work motivation. Based on the results of this study conclude that all hypothesis are supported but one hypotheses that examine the influence of organizational culture has no effect on work motivation https://doi.org/10.26905/jmdk.v5i2.1570